Navigating Speaking Problems: Insights from an Indonesian EFL Learner’s Experience - Saputra, Eko Restu; Suryati, Nunung (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
Indonesian EFL (English as a Foreign Language) learners frequently encounter challenges when speaking English in formal settings. Thus, this study aims to explore the problems faced by a low-performing student and the solutions to the problems. The participant of this study was an English Department student of Universitas Negeri Malang who was taking the Speaking for Academic Purposes course in the study. A case study methodology was employed to address the research questions, utilizing an observation checklist protocol for data analysis during the observation phase, as well as a three-stage qualitative data analysis approach for the semi-structured interview data. The result showed that the participant encountered affective, social, and linguistic problems. To address these problems, the participant expressed that regular practice of English would be beneficial, along with the integration of technology into the learning process to enhance effectiveness. The participant, likewise, emphasized the importance of teacher involvement, advocating for the provision of ample opportunities for students to engage in speaking activities. In addition, teachers should be mindful of cultivating an optimal learning environment that positively influences classroom dynamics. The findings of this study may serve as a valuable reference for teachers addressing problems faced by low-performing students in English speaking.